EFFICACY OF MISOPROSTOL TREATMENT ON EXPULSION OF DEAD FOETUSES RETAINED IN-UTERO - X, SOPHIA; C, JAYAKUMAR; J, DEEPAK; R S, ABHILASH (The Indian Journal of Animal Reproduction, 2022)
A great challenge in canine obstetrics is averting a caesarean section particularly in a partially delivered litter with one or two non viable foetuses remaining in utero. Response to routine medical management with calcium and oxytocin in many of these delayed cases will be deficient. The efficiency and safety of misoprostol (PGE1) for augmentation and completion of whelping in such dystocic dogs were studied. Nine of the ten dogs (90%) responded to misoprostol administration, of which eight dogs experienced unassisted expulsion of foetuses and in one dog the foetus was removed using whelping forceps. Induction of foetal expulsion with misoprostol reduced the rate of caesarean section in dogs with partial uterine retention of dead foetuses.